Espaços e tempos da educação infantil: investigando a ação pedagógica com os bebês - Flavia de Oliveira Coelho (2015)
The organization of space and time plays a central role in daily life of early childhood institutions. The objective of this research was to investigate how spaces and times are organized, for babies aged between 1 and 2 years, who were enrolled in full workday at a public nursery in the city of Governador Valadares. The survey sought to identify how babies experience the routines, spaces and times settled for them, and how these elements are part of the pedagogical conduct. In observation of space and time organization, the survey sought to establish how these elements favor the interactions between babies, with adults and the materials that make up Nursery setting. The methodology consisted of a qualitative approach, with an interpretative nature, by conducting a case study, using participant observation and performing interviews with the teachers. The records were made by photos, notes in a diary and video recording. Analyses revealed that the ways of space and time organization regulates the possibilities of action by babies and teachers in nursery setting. Similarly, it can favor the interactions that babies establish among themselves and with adults, as well as exploration of different materials and spaces where they circulate. The research established a dialogue with literature, based on the theoretical framework of Childhood Sociology and historic-cultural approach, especially with those dealing with the presence of babies in nurseries, such as Tristan (2004), Schmitt (2008) and Gobatto (2011). The study showed that it is in the interaction with pairs that babies operate in an active mode,sharing emotions, conflicts, appropriating of the setting rules, as well as enhancing their experiences and cultural practices ensemble. In this sense space organization must be thought in favor of these interactions as it constitutes another education element; on the other side, time organization should be a flexible enough, in order to face babies needs. The pedagogical conduct with babies should consider their needs and, above all, their intentions and multiple forms of communication.